2013
DOI: 10.4082/kjfm.2013.34.4.228
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant Use and Diabetes Mellitus Risk: A Meta-Analysis

Abstract: BackgroundEpidemiologic studies have reported inconsistent findings regarding the association between the use of antidepressants and type 2 diabetes mellitus (DM) risk. We performed a meta-analysis to systematically assess the association between antidepressants and type 2 DM risk.MethodsWe searched MEDLINE (PubMed), EMBASE, and the Cochrane Library (through Dec 31, 2011), including references of qualifying articles. Studies concerning the use of tricyclic antidepressants (TCAs), selective serotonin reuptake i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 45 publications
(80 reference statements)
3
48
0
1
Order By: Relevance
“…In summary, although SSRIs as a drug class are typically believed to increase the risk of DM2 [82] , current clinical evidence supports this notion predominantly for fluvoxamine and paroxetine [75] . This underlines the importance of pondering the metabolic profiles for each individual SSRI, especially in subjects with risk factors for DM2 or CVD.…”
Section: Prospective Cohort Study Including 97 Female Patients With Gmentioning
confidence: 98%
“…In summary, although SSRIs as a drug class are typically believed to increase the risk of DM2 [82] , current clinical evidence supports this notion predominantly for fluvoxamine and paroxetine [75] . This underlines the importance of pondering the metabolic profiles for each individual SSRI, especially in subjects with risk factors for DM2 or CVD.…”
Section: Prospective Cohort Study Including 97 Female Patients With Gmentioning
confidence: 98%
“…On the other hand, there are clinical data showing that chronic administration of SSRI into nondiabetic patients can lead to insulin resistance and lipid metabolism disorders [268,269]. These data may be explained by the fact that a long-term increase of brain serotonin level above norm induces hyperactivation of serotonin signaling, resulting in the abnormalities of feeding behavior, energy expenditure and insulin sensitivity, and, in addition, leads to the changes in the circadian rhythm.…”
Section: Serotonin Signaling Systemmentioning
confidence: 99%
“…Treatment decisions are therefore often based on data from younger adults [112]. Antidepressants have been reported to affect glycaemic control and to trigger the onset of type 2 DM [115][116][117][118][119]. It is difficult to differentiate between the possible diabetogenic side effects of antidepressants per se (such as weight gain), from the effects associated with the depressive disorder [116,119].…”
Section: Antidepressants In Elderly Patientsmentioning
confidence: 99%
“…Antidepressants have been reported to affect glycaemic control and to trigger the onset of type 2 DM [115][116][117][118][119]. It is difficult to differentiate between the possible diabetogenic side effects of antidepressants per se (such as weight gain), from the effects associated with the depressive disorder [116,119]. SSRIs have been reported to confer a glucose lowering effect [117,120] and animal model studies have reported glucose increment from TCAs [121].…”
Section: Antidepressants In Elderly Patientsmentioning
confidence: 99%